The hepatoprotective effect of aqueous extracts of Penthorum chinense Pursh against acute alcohol-induced liver injury is associated with ameliorating hepatic steatosis and reducing oxidative stress. Issue 5 (13th May 2015) - Cao, Yi-Wei; Jiang, Yun; Zhang, Da-Yong; Zhang, Xiao-Jing; Hu, Yuan-Jia; Li, Peng; Su, Huanxing; Wan, Jian-Bo
<x xml:space="preserve">Abstract</x> Aqueous extracts of Penthorum chinense Pursh, a health food and folk medicine, protects against acute alcohol-induced liver injury.